EKSTRAKSI KULIT JERUK LEMON (Citrus Limon) DENGAN VARIASI PERLAKUAN BAHAN DAN DAYA MENGGUNAKAN METODE MICROWAVE ASSISTED EXTRACTION (MAE) - Cindiya, Annisa Nur Oktari; Islami, Nurdini; Muyassaroh (Teknik Kimia ITN Malang, 2023)
Lemon (Citrus limon (L.)) is one of the natural ingredients that can be utilized fruit and its skin contains a source of vitamin C, antioxidants, carbohydrates, potassium, folate, calcium, thiamin, niacin, vitamin B6, phosphorus, magnesium, and other compounds. This study aims to obtain limonene content and high yield. The components of orange peel oil consist of limonene (95%), mirsen (2%), noctanal (1%), pinece (0.4%), linanool (0.3%), sabiene (0.2%), geranial (0.1%), neral (0.1%, dodecanal (0.1%), others (0.5%). In this study, the method used was Microwave Assisted Extraction, using 2 factors with microwave power (100, 200, 300 and 399 watts) and material treatment (fresh, aerated, in the oven and under the sun). The best results in this study were obtained in the processing of materials dried by oven using a temperature of 45⁰C for 2 hours using the operating conditions of 399 W microwave power producing yellow oil, smelling very strong lemon, having a yield of 0.0936%, and limonene content of 34.512%.